If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying x^{2}+ 16x = -7 Reorder the terms: 16x + x^{2}= -7 Solving 16x + x^{2}= -7 Solving for variable 'x'. Reorder the terms: 7 + 16x + x^{2}= -7 + 7 Combine like terms: -7 + 7 = 0 7 + 16x + x^{2}= 0 Begin completing the square. Move the constant term to the right: Add '-7' to each side of the equation. 7 + 16x + -7 + x^{2}= 0 + -7 Reorder the terms: 7 + -7 + 16x + x^{2}= 0 + -7 Combine like terms: 7 + -7 = 0 0 + 16x + x^{2}= 0 + -7 16x + x^{2}= 0 + -7 Combine like terms: 0 + -7 = -7 16x + x^{2}= -7 The x term is 16x. Take half its coefficient (8). Square it (64) and add it to both sides. Add '64' to each side of the equation. 16x + 64 + x^{2}= -7 + 64 Reorder the terms: 64 + 16x + x^{2}= -7 + 64 Combine like terms: -7 + 64 = 57 64 + 16x + x^{2}= 57 Factor a perfect square on the left side: (x + 8)(x + 8) = 57 Calculate the square root of the right side: 7.549834435 Break this problem into two subproblems by setting (x + 8) equal to 7.549834435 and -7.549834435.## Subproblem 1

x + 8 = 7.549834435 Simplifying x + 8 = 7.549834435 Reorder the terms: 8 + x = 7.549834435 Solving 8 + x = 7.549834435 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = 7.549834435 + -8 Combine like terms: 8 + -8 = 0 0 + x = 7.549834435 + -8 x = 7.549834435 + -8 Combine like terms: 7.549834435 + -8 = -0.450165565 x = -0.450165565 Simplifying x = -0.450165565## Subproblem 2

x + 8 = -7.549834435 Simplifying x + 8 = -7.549834435 Reorder the terms: 8 + x = -7.549834435 Solving 8 + x = -7.549834435 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + x = -7.549834435 + -8 Combine like terms: 8 + -8 = 0 0 + x = -7.549834435 + -8 x = -7.549834435 + -8 Combine like terms: -7.549834435 + -8 = -15.549834435 x = -15.549834435 Simplifying x = -15.549834435## Solution

The solution to the problem is based on the solutions from the subproblems. x = {-0.450165565, -15.549834435}

| 3x^2-24x+1=0 | | 5x^2+6xy+13j^2= | | 2x^2+14x=120 | | 6r^2+11r-10=0 | | 6r^2+10r=0 | | y=4k^2+6k-1 | | 3x^2+16x+64=0 | | 2x^2+8x=90 | | 3x^2+12x=180 | | 4x^2+13x-75=0 | | 4x^2+13-75=0 | | 3x^2+10x-88=0 | | 2v^2-4v+52= | | v^2-4v+16= | | v^2-36= | | 24uxy^5-22u^5y^5= | | 4u^6+6u^5-10u^4= | | 10x^2+12x+18=0 | | 25p^2=4 | | 5x^2=13x+6 | | x^2+10x+25=0 | | X^2+4x+4=0 | | x^2+6x+9=0 | | -4x=2x^2-6 | | -x=2x^2-6 | | -2x=3x^2-1 | | -9x=2x^2-5 | | x^2-5x-6=0 | | x^2-x-12=0 | | 3x^2+5x-13=11-9x | | 5x^3-5x=0 | | 16x^2+2x-3=0 | | 4x^2-25=0 | | x^2-19x=0 | | x^2-x+18=0 | | 13x^2-11x=0 | | 7x^2+4x-15=49-44x | | 3x^3+9x^2+6x=0 | | x^2-3x-18=0 | | x^2-63x+60=0 | | 2x(4x-7)+3=(2x-7)(3x+4)+2x^2 | | 8x^3+10xy+6x^2y^5=0 | | 2X(X^2-4X+7)= | | 2x^2-5x-5=0 | | 2x^2-38x=7x^2-3x-24 | | 9p^2+18p=10 | | x^2-5x=6 | | 2x^2-4=-204 | | 2x^2-8=-170 | | x(5x+10)=2x^2-3x+30 | | 8x^2-8x-1=0 | | 2x^2-9x-2=0 | | 2x^2=10x+3 | | y^2-4y+8=0 | | 42t^2-13tv-42v^2= | | 6s^2-13s+6= | | 2w^2+9w+9= | | 4x^7-20x^5+16x^8= | | x^2-16=0 | | x^2=81 | | 3x^2+6x=0 | | x^2-7x=0 | | y^2+6y+8=0 | | 5x^4+31x^2+6=0 | | x^2-10-4x-11=0 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion
- Tip calculator
- Numbers as decimals, fractions, percentages
- More or less than - questions